Unveiling the evolutionary relationships and the high cryptic diversity in Andean rainfrogs (Craugastoridae: Pristimantis myersi group) - Franco-Mena, Daniela (2023)
Background. Pristimantis is the most diverse genus of terrestrial frogs. Historically, it has been divided into several phenetic groups in order to facilitate species identification. However, in light of phylogenetic analysis, many of these groups have been shown to be non-monophyletic, denoting a high degree of morphological convergence and limited number of diagnostic traits. In this study, we focus on the Pristimantis myersi group, an assemblage of small rainfrogs distributed throughout the Andes of Ecuador and Colombia, whose external morphology is highly conserved, and its species diversity and evolutionary relationships largely unknown. Methods. We inferred a new phylogenetic hypothesis for the frog genus Pristimantis, including all available sequences of the mtDNA 16S rRNA, as well as new DNA sequences from 175 specimens. Our sampling included 19 of the 24 species currently recognized as part of the Pristimantis myersi group. Results. Our new evolutionary hypothesis recovered the P. myersi group as non-monophyletic and composed of 16 species. Therefore, we exclude P. albujai, P. bicantus, P. sambalan, and P. nelsongalloi in order to preserve the monophyly of the group. We discovered at least eight candidate species, most of them hidden under the names of P. leoni, P. hectus, P. festae, P. gladiator, and P. ocreatus. Discussion. Our results reveal the occurrence of a high level of cryptic diversity to the species level within the P. myersi group and highlight the need to redefine some of its species and reassess their conservation status. We suggest that the conservation status of six species within the group need to be re-evaluated because they exhibit smaller distributions than previously thought; these species are: P. festae, P. gladiator, P. hectus, P. leoni, P. ocreatus, and P. pyrrhomerus. Finally, given that the Pristimantis myersi group, as defined in this work, is monophyletic and morphologically diagnosable, and that Trachyphrynus is an available name for the clade containing P. myersi, we implement Trachyphrynus as a formal subgenus name for the Pristimantis myersi group.